Design and characterization of a tissue‐engineered bilayer scaffold for osteochondral tissue repair†. (21st November 2012) - Giannoni, Paolo; Lazzarini, Erica; Ceseracciu, Luca; Barone, Alberto C.; Quarto, Rodolfo; Scaglione, Silvia
Abstract Treatment of full‐thickness cartilage defects relies on osteochondral bilayer grafts, which mimic the microenvironment and structure of the two affected tissues: articular cartilage and subchondral bone. However, the integrity and stability of the grafts are hampered by the presence of a weak interphase, generated by the layering processes of scaffold manufacturing. We describe here the design and development of a bilayer monolithic osteochondral graft, avoiding delamination of the two distinct layers but preserving the cues for selective generation of cartilage and bone. A highly porous polycaprolactone‐based graft was obtained by combining solvent casting/particulate leaching techniques. Pore structure and interconnections were designed to favour in vivo vascularization only at the bony layer. Hydroxyapatite granules were added as bioactive signals at the site of bone regeneration. Unconfined compressive tests displayed optimal elastic properties and low residual deformation of the graft after unloading (< 3%). The structural integrity of the graft was successfully validated by tension fracture tests, revealing high resistance to delamination, since fractures were never displayed at the interface of the layers (n = 8). Ectopic implantation of grafts in nude mice, after seeding with bovine trabecular bone‐derived mesenchymal stem cells and bovine articular chondrocytes, resulted in thick areas of mature bone surrounding ceramic granules within the bony layer, and a cartilaginous alcianophilic matrix in the chondral layer. Vascularization was mostly observed in the bony layer, with a statistically significant higher blood vessel density and mean area. Thus, the easily generated osteochondral scaffolds, since they are mechanically and biologically functional, are suitable for tissue‐engineering applications for cartilage repair. Copyright © 2012 John Wiley & Sons, Ltd.